Request Strategies of EFL University Learners at Jambi University - Kurniawan, Raju; Fussalam, Yahfenel Evi; Abrar, Mukhlash (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2024)
Making appropriate requests is a crucial aspect of pragmatic competence in language learning. This research aimed to investigate common request strategies used by EFL University Learners at Jambi University when making requests at the ages of 19, 20, and 21. This research design was an intrinsic case study to gain an in-depth knowledge of the phenomenon within its specific context. Data were collected through a written discourse completion test (DCT) from six participants, two from each age group. They were analyzed using discourse analysis, specifically focusing on the request strategies proposed by Blum-Kulka and Olshtain (1984), Blum-Kulka (1987), and Trosborg (1995). The findings reveal that most participants employed conventionally indirect (hearer-based) strategies in the form of ability, willingness, and permission (25 times, 83.3% frequency of semantic formulas) and conventionally indirect request (speaker-based) strategies in the form of desires/needs (3 times, 10% frequency of semantic formulas), followed by direct request strategies in the form of performatives (2 times, 6.6% frequency of semantic formulas). The research concluded that conventionally indirect request strategies (hearer-based) in the form of ability, willingness, and permission are mostly used in making requests among the studied age groups. It also found that age influenced how social power as a social variable maintained smooth social interactions in making requests. Those different age groups exhibited diversities in the use of directness level in making requests based on the age gap between the speaker and the hearer. Additionally, the research indicates how the focus shifts to the hearer's wants as the speaker casts requests in various direct forms. This suggests that people tend to make requests subtly, especially within academic settings. These findings have important implications for language teaching and pragmatics instruction, potentially influencing approaches to improving learner awareness of appropriate request strategies in academic and social contexts.